2021
DOI: 10.1177/20503121211022197
|View full text |Cite
|
Sign up to set email alerts
|

Baclofen therapeutics, toxicity, and withdrawal: A narrative review

Abstract: Baclofen is an effective therapeutic for the treatment of spasticity related to multiple sclerosis, spinal cord injuries, and other spinal cord pathologies. It has been increasingly used off-label for the management of several disorders, including musculoskeletal pain, gastroesophageal reflux disease, and alcohol use disorder. Baclofen therapy is associated with potential complications, including life-threatening toxicity and withdrawal syndrome. These disorders require prompt recognition and a high index of s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
67
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 81 publications
(79 citation statements)
references
References 122 publications
(243 reference statements)
1
67
0
Order By: Relevance
“…The recent expansion in the use of baclofen to treat spasticity of different causes has been associated with a significant increase in its complications, including toxicity events and withdrawal syndrome, especially regarding intrathecal baclofen administration [3]. In particular, withdrawal syndrome is observed frequently after sudden cessation of intrathecal baclofen administration mainly due to pump malfunction, migration of the intrathecal catheter, or, as in our case, removal of the pump after infection [10,11].…”
Section: Discussionmentioning
confidence: 91%
See 2 more Smart Citations
“…The recent expansion in the use of baclofen to treat spasticity of different causes has been associated with a significant increase in its complications, including toxicity events and withdrawal syndrome, especially regarding intrathecal baclofen administration [3]. In particular, withdrawal syndrome is observed frequently after sudden cessation of intrathecal baclofen administration mainly due to pump malfunction, migration of the intrathecal catheter, or, as in our case, removal of the pump after infection [10,11].…”
Section: Discussionmentioning
confidence: 91%
“…Baclofen, an agonist for gamma-aminobutyric acid (GABA) receptors [1], is an effective therapeutic mainly for the treatment of spasticity related to spinal cord injuries, other spinal cord diseases, and multiple sclerosis [2]. In recent years, however, as its clinical use has increased-such as for treatment of musculoskeletal pain and muscle spasm-its poten-tial side effects, including life-threatening toxicity and withdrawal syndrome, have become more frequent [3]. Baclofen toxicity and withdrawal syndrome, especially when related to intrathecal administration, can often determine severe multisystem organ failure requiring admission to the intensive care unit (ICU) to administer supportive measures to ensure vital sign stability.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…7,34 Thus, the clear first-line option for treatment is parenteral therapy. 35 The parenteral agent with which the most experience has been gained is diazepam.…”
Section: Withdrawalmentioning
confidence: 99%
“…Studies suggested that toxicity is likely dose-dependent and more common at doses greater than 200mg [4,5]. It is worth noting that severe baclofen withdrawal may occur within hours to days of sudden cessation or dose reduction and is mostly associated with altered mental status, hallucinations, worsening spasticity, and fever [6] The usual maximum daily dose of oral baclofen is 80mg [1], although some patients require up to 120mg/day [7]. Toxicity with high doses is seen in accidental or intentional overdose and patients requiring intrathecal baclofen [3].…”
Section: Introductionmentioning
confidence: 99%